2014
DOI: 10.1080/19440049.2014.933491
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic speciation in rice-based food for adults with celiac disease

Abstract: Celiac disease (CD) may affect up to 1% of the Western population. It is a disease whose diagnosis has been made mainly in childhood, but now the profile has changed, with one out of five newly diagnosed individuals being over 65 years old. The only treatment for this population is a gluten-free diet. Therefore, the objective of this study was to analyse the occurrence of arsenic (As) in gluten-free products, basically those rice-based, intended for celiac adult consumers. The current study demonstrated that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
2
23
1
Order By: Relevance
“…All samples were analyzed for t‐As by Hydride Generation Atomic Absorption Spectrometry (HG‐AAS). In this analysis, 1 g of dried, ground and homogenized rice samples was weighed and digested using the method described by Muñoz and others () and later slightly modified by Munera‐Picazo and others (, ). Calibration standards of NaAsO 2 [arsenite, As (III)] were prepared using the same HCl concentration of the samples and certified reference materials (CRM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All samples were analyzed for t‐As by Hydride Generation Atomic Absorption Spectrometry (HG‐AAS). In this analysis, 1 g of dried, ground and homogenized rice samples was weighed and digested using the method described by Muñoz and others () and later slightly modified by Munera‐Picazo and others (, ). Calibration standards of NaAsO 2 [arsenite, As (III)] were prepared using the same HCl concentration of the samples and certified reference materials (CRM).…”
Section: Methodsmentioning
confidence: 99%
“…In the case of Iran, the daily consumption per capita of milled rice in 2009 was 63 g/person/d (FAOSTAT ). In the last decade, it has been demonstrated that the problem of high contents of As in foods can also affect other countries apart from India and Bangladesh, such as the United States, China, and the EU (Carbonell‐Barrachina and others ; Munera‐Picazo and others , ; Williams and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Rice is therefore essential for the manufacture of supplies for celiac disease-affected people and reaches high percentages in their formulations. 67,68 Munera-Picazo et al 69,70 conducted two studies evaluating the occurrence of As in foods intended for children and adults who suffer from celiac disease. A positive relationship between rice percentage and As content was clearly observed (Figure 4).…”
Section: Celiac Disease and Lactose Intolerancementioning
confidence: 99%
“…Results of two studies on rice milk proved that all samples of the EU and the US fail the maximum residue limit established for water (10 µg L -1 ). 70,72 …”
Section: Celiac Disease and Lactose Intolerancementioning
confidence: 99%
“…): 36 results were found from several authors, 37,39,40,162,[180][181][182][183]187,190,193,195,197,198,200,239,241,251,[266][267][268][269][270][271][272][273][274] whereas only one researcher used the HPLC-HG-AFS coupled system. 275 Several authors use non-coupled HG as a previous step to measuring iAs with different techniques. Five publications from the same group use FI-HG-AAS to determine iAs content; [147][148][149][150][151] while two authors apply an HG-AFS system: one with a prior SPE step, 155 and the other without SPE.…”
Section: Referencesmentioning
confidence: 99%